A STUDY ON BACTERIOLOGICAL PROFILE OF SURGICAL SITE INFECTION AND THEIR ANTIMICROBIAL SUSCEPTIBILITY PATTERN AT A TERTIARY CARE HOSPITAL IN TIRUPATI - S., PAVADHARANI; RAVIPRAKASH, G. N.; K., PRASANNA LAKSHMI; N., SRIVANI; LAVANYA, VALLURI ANITHA (International Journal of Current Pharmaceutical Research, 2025)
Objective: Surgical Site Infections (SSIs) are defined as infections apparent within 30days of an operative procedure and most often between the 5th and 10th postoperative days. It constitutes a major public health problem worldwide; It is one of the most common causes of nosocomial infection. They are responsible for increasing the treatment cost, length of hospital stays and significant morbidity and mortality. Despite the technical advances in infection control and surgical practices, SSI still continue to be a major problem, even in hospitals with most modern facilities. The present study conducted to isolate and identify microbes from pus samples collected from patients who were suspected for SSI and to determine their antimicrobial susceptibility profiles in a tertiary care hospital. Methods: This is a cross-sectional study conducted in the Department of Microbiology, Sri Venkateswara Medical College, Tirupati for a period of 6 mo. A total of 390 various clinical samples were collected and processed. Isolates were tested for antibiotic susceptibility by a Kirby-Bauer disk diffusion method. Results: Out of 390 pus/wound discharge samples processed, 132 (34%) samples were culture positive, among which 107 (81%) were Gram-negative bacilli and 25 (19%) were Gram-positive cocci. Male to female ratio was 2:1. Most common age group affected was>50yrs. Predominant isolates were Klebsiella pneumoniae (73.47%) followed by Pseudomonas aeruginosa (26.53%) and Staphylococcus aureus (17.4%). Gram-negative bacilli showed maximum susceptibility to Imipenam, Piperacillin-Tazobactam and Amikacin and Gram-positive cocci showed 100% to Linezolid, Vancomycin. Conclusion: SSI remains to be a significant challenge for the surgeon’s inspite of sterile surgical techniques and prophylactic use of antibiotics. Hospital infection control measures like hand hygiene, strict adherence to pre-operative measures, rational use of antibiotics and establishing active surveillance can reduce the prevalence of SSIs.